Research Confidence of Critical Care Nurses: A Mixed Methods Preliminary Study - Mary Grace Anne P. Batalla; Jeffrey R. Salazar (Nursing in Critical Care, 2026)
ABSTRACT Gaining competencies in the research process is difficult and labour‐intensive, especially if the nurse has no prior experience in research engagement. The aim of this paper was to examine the research confidence of critical care nurses. This preliminary study utilised a mixed methods design. Critical care nurses working in the United Kingdom participated in the study. A survey questionnaire and focus group discussions (FGD) were used to collect data. Findings showed that nurses had moderate levels of confidence in research skills. Thematic analyses of FGD responses highlighted the organisational barriers to and the role of the research link nurse in increasing nurses' confidence in research activities. As such, healthcare organisations should take steps to boost confidence in research. Nurses who feel confident in engaging and participating in research activities are ideally positioned to maximise the benefits of research in clinical practice.